An integrated mental health and vocational intervention: A longitudinal study on mental health changes among young adults - Ulrika Liljeholm; Elisabeth Argentzell; Ulrika Bejerholm (Wiley, 2020)
Abstract Aim This study aimed to investigate changes in mental health among young adults participating in an integrated mental health and vocational support intervention according to the Södertälje Supported Employment and Education model. Design A prospective longitudinal pre-post intervention study of 12 months. Methods Instruments on depressive symptoms, quality of life, empowerment, engagement in activities and sociodemographic characteristics were administered to 42 young adults aged 19-28 years with mood disorders. Wilcoxon signed rank tests were used to assess changes in mental health. Results Statistically significant positive changes between baseline and 12 months were noted for quality of life and engagement in activities. Difference in empowerment scores neared significance and a statistical trend towards lower depression scores was seen, corresponding to moderate depression at baseline and less severe depression at 12 months. Conclusions Integrated mental health and vocational services may support young adults' mental health and is suggested to be linked to their personal recovery and clinical recovery.